State-Trait Anxiety Vis-A-Vis Linguistic Competence Among Sophomore College Students of Western Mindanao State University - Selisana, Mario Mark B. (Langkit : the Official journal of the College of Arts & Social Sciences Mindanao State University-Iligan Institute of Technology, 2016)
This study was undertaken to determine the state-trait anxiety and linguistic competence of WMSU sophomore college students. The objectives were to measure the degree of difference in state- trait anxiety and the linguistic competence of college students according to gender and course and to determine whether there is a significant relationship. Descriptive-Correlational Quantitative Research Design was used and Systematic Listing Sampling Procedure was utilized. Data were collected using State-trait Anxiety Inventory (STAI) adapted from Spielberger (1991), and the Linguistic Competence Test (LCT) on grammar and vocabulary used by Salian (2012). The results showed that the sophomore college students of WMSU had "moderate anxiety" based on STAI. In terms of grammar and vocabluary, the LTC results showed that the respondents were classified as "very good user". There is a significant relationship between their state-trait anxiety and their linguistic competence, but gender and course of the respondents did not influence their state-trait anxiety and linguistic competence. Since moderate state-trait anxiety can influence college students' high linguistic competence, there is a need to expose them to challenging language classroom activities. Gender and course do not affect state-trait anxiety and linguistic competence which may be indicative of the progressive benefits on the part of the language learning instructor and the English department curriculum. Contrary to traditional notion that females outperform males in linguistic competence task, the similar output of males compared to females here can be viewed as progress report for WMSU college students